An Efficient Method of Load Forecasting for Non-Working Days - Ireri, T.G; Abungu, N.O; Murage, D.K (My University, 2012)
A new efficient method is proposed to forecast the non-working days load demand at Ruiru substation which is a 66/11kv; 66/33kv distribution substation located along Thika road. The forecasts are based on the total daily load the substation supplies in the area which constitutes domestic, commercial and industrial loads. It is based on making the non-working days load demand a function of working days load. This method simplifies the load estimation of load demand on weekends. A lot more time is spent in computation of working days load demand using classical methods. Weekends loads are made a function of load forecasts for normal working days. This simplifies load forecasts for non-working days in that the rigorous computations are avoided thus saving time in load prediction. Through this method the numerical coefficient of weekends loads(C) is determined for its ith hour of the load for the chosen day in a month for a particular substation. The result has shown that the method is efficient with high accuracy and robust. The error margin of the weekend loads estimates was established as 1.69%.
Keywords: Load forecast; Working days load demand; no - working days demand load; Numerical coefficient.